Disabled consumers in solidary private law - Lúcia Souza d'Aquino; Guilherme Mucelin (Revista da Faculdade de Direito da Universidade de Uberlândia, 2020)
This work analyzes the evolution of private law, centered on individualism and totalizing codification, towards private law of solidarity, centered on solidarism, which valorizes the person before his particularities and his laws of protection. Thus, with the strengthening of constitutional principles and human rights, the disabled person is described, as a consumer, as hypervulnerable, worthy of specific protection, which will only be effective with the dialogue between the Consumer Protection Code and the Status of the Disabled Person. The research problem centers on how to protect the disabled person as a consumer from the plurality of standards that affect this relationship, in particular the Consumer Protection Code and the Status of Persons with Disabilities. Using a hypothetical methodology, it is assumed that the dialogue of sources method is the appropriate means to effectively protect people with disabilities in the consumer market